PENGARUH MODEL PEMBELAJARAN AUDITORY, INTELLECTUALY, REPETITION BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KOMPETENSI PENGETAHUAN IPA - ayu Yunita Dewi (Indonesian Journal Of Educational Research and Review, 2018)
This research was aimed at determining the significant differences regarding knowledge competence of science between groups of students applying auditory, intellectualy, repetition learning model using audio visual media with group of students who applied conventional learning in grade IV of SD Gugus Kompyang Sujana in North Denpasar, academic year 2017/2018. The type of research used was quasi experiment by using non-equivalent group design. The population of this study were 346 students covering all the fourth graders of SD Gugus Kompyang Sujana in North Denpasar, academic year 2017/2018. Sampling was done by group sample technique, which was held by doing random in class group, so that the following results were obtained; IVA grade of SD Negeri 4 Tonja as experiment class and IV grade of SD Negeri 4 Peguyangan as control class. The result of calculation of "gain" data score showed the average value of science knowledge competence of experimental class students was higher than the average knowledge competence of science students of control class (experiment = 0,63 > control = 0,50). Hypothesis testing was analyzed using the t-test with the formula "polled variance". Testing criteria at significance level of 5% and dk = 80. Provided tcount value = 4,157 > ttable value = 2,000 This means that there were significant differences regarding knowledge competence of science in groups of students applying auditory, intellectualy, repetition learning model using audio visual media with group of students who applied conventional learning in grade IV of SD Gugus Kompyang Sujana in North Denpasar, academic year 2017/2018. Thus, auditory, intellectualy, repetition learning model using audio visual media have an effect on science knowledge competence of fourth grader students of SD Gugus Kompyang Sujana in North Denpasar in academic year 2017/2018.